Proceedings: 1993 Colorado water convention: Front Range water alternatives and transfer of water from one area of the state to another - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 1993)
Convention was held on January 4-5, 1993 in Denver, Colorado.
1993 Colorado water convention
Front Range water alternatives and transfer of water from one area of the state to another
Keywords: Water transfer -- Colorado -- Congresses; Water-supply -- Government policy -- Colorado -- Congresses; Water-supply -- Front Range (Colo. and Wyo.) -- Congresses